Transition in the Perception of Cultural Practices through Modernization The Acceptance of Polygyny among Njinikoms of Southern Cameroon - Tanyi, Mauren (My University, 2009)
This study explains the reasons why people contracted polygynous marriages in Njinikom between the 60s and 2006 and how this has undergone a transition from a traditional society to a modern one. This explanation for the transition is made by referring to theories on the occurrence of polygyny in society prior to and within the 80s and examine if these theories are still applicable or not and what changes have taken place. The data was collected using in-depth interviews with ten polygynous persons from Njinikom. With evidence from Njinikom, a transition in the motives and form of polygyny is discussed. Education, urbanization, and migration are used to explain this transition. Polygyny in this society has undergone some changes with modernity. According to theories on the existence of polygyny in society, men formerly practised polygyny because they needed additional hands on the farm. Today, because of the changing environment due to the infiltration of new cultures, the story is different. Women prefer men who are able to care for them and their children. Also, some women prefer to maintain paternity for their children if they already have children with married men. For the men, migration and the poor health of their first wives result in polygyny. This culture is deeply rooted in such a way that, despite the financial implications of a large family (mostly because of the costs of educating children), some men still find it desirable to get additional wives. Education, migration, industrialization and modernity have changed the motives behind polygyny. Legal polygyny is not so common. Instead, polygyny has taken a new form, which is that of informal relationships or “outside wives”.
Keywords: Polygyny; culture; transformation; modernization; Africa; Cameroon; Njinikom; fi=Englannin kieli|en=English language|; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|